Multyprint Enterprise / Mohd Shaikhul Rafjan Sani Zakaria ... [et al.] - Zakaria, Mohd Shaikhul Rafjan Sani; Abdullah, Nurzailawati; Ali, Muhammad Wizam; Hamat, Shahroirwan; Ghazali, Rafidah (Faculty of Applied Sciences, 2003)
MultyPrint Enterprise is a company, which supply services of photocopy and retail various papers to an individual, especially student in area Seksyen 7, Shah Alam.